Дослідження напруженого стану робочих лопаток парових турбін та підвищення їх експлуатаційної надійності - Фурсова, Тетяна Миколаївна (НТУ "ХПІ", 2016)
Проведено дослідження напруженого стану одного з найбільш відповідальних елементів парової турбіни – робочої лопатки – за допомогою чисельного методу кінцевих елементів. Встановлено загальну картину розподілу напруг, проаналізовані зони, що представляють найбільшу небезпеку пошкоджень внаслідок силової та геометричної концентрації напруг. Розглянуті технологічні та конструктивні міри для підвищення експлуатаційної надійності робочих лопаток та забезпечення безаварійної роботи турбіни.

In the operating conditions of turbine machines many rotor blades experience the fatigue failure and the cracks originate in the zones with a maximum stress level. The purpose of this scientific paper is to study the stressed state of the rotor blade of steam turbine in the three-dimensional problem statement using the numerical method of final elements and analyzing the ways of improvement of their operational reliability. The distribution of stresses in blades’ elements containing angular transition zones with high load-bearing and geometric concentrations of stresses, in particular the tail connection, the active blade part-to-tail blade unit transition zone, the blade nib (active part)-to-shroud transition zone was analyzed for the rotor blade of the third stage of LPC of К-300-240 turbine. Technological and structural solutions were given to increase the operational reliability of rotor blades. These include the use of electroerosion machining for manufactured blades, strengthening the surfaces of angular transition zones of the tail connections of rotor blades exposing them to surface plastic stresses, i.e. bead blasting treatment, increasing angular transition radii, especially blade butts, using integral-milled shrouds that are used for the annular connection of blades on the rotor wheel. The data given in this paper can be used for the turbine building branch and also for the design and operation of steam turbines. These data can also be used for the prevention of possible failures in stress concentration zones.
Investigating the stressed state of the rotor blades of steam turbines to increase their operation reliability
Keywords: метод кінцевих елементів; геометрична концентрація напруг; МКЕ; турбомашини; low pressure cylinder